A Cost-Utility Analysis of the Use of Preoperative Computed Tomographic Angiography in Abdomen-Based Perforator Flap Breast Reconstruction. Issue 4 (April 2015) - Offodile, Anaeze C.; Chatterjee, Abhishek; Vallejo, Sergio; Fisher, Carla S.; Tchou, Julia C.; Guo, Lifei
<x xml:space="preserve">Abstract</x> Background: Computed tomographic angiography is a diagnostic tool increasingly used for preoperative vascular mapping in abdomen-based perforator flap breast reconstruction. This study compared the use of computed tomographic angiography and the conventional practice of Doppler ultrasonography only in postmastectomy reconstruction using a cost-utility model. Methods: Following a comprehensive literature review, a decision analytic model was created using the three most clinically relevant health outcomes in free autologous breast reconstruction with computed tomographic angiography versus Doppler ultrasonography only. Cost and utility estimates for each health outcome were used to derive the quality-adjusted life-years and incremental cost-utility ratio. One-way sensitivity analysis was performed to scrutinize the robustness of the authors' results. Results: Six studies and 782 patients were identified. Cost-utility analysis revealed a baseline cost savings of 3179, a gain in quality-adjusted life-years of 0.25. This yielded an incremental cost-utility ratio of −12, 716, implying a dominant choice favoring preoperative computed tomographic angiography. Sensitivity analysis revealed that computed tomographic angiography was costlier when the operative time difference between the two techniques was less than 21.3 minutes. However, the clinical advantage of computed tomographic angiography over Doppler ultrasonography only showed that computed tomographic angiography would still remain the cost-effective option even if it offered no additional operating time advantage. Conclusions: The authors' results show that computed tomographic angiography is a cost-effective technology for identifying lower abdominal perforators for autologous breast reconstruction. Although the perfect study would be a randomized controlled trial of the two approaches with true cost accrual, the authors' results represent the best available evidence.